Narrative Review: A Comparative Analysis Of The Effectiveness Of Insulin And OAD Treatment in BPJS Outpatients Patients With Type 2 Diabetes Mellitus Various Hospitals In Indonesia - Wina Oktaviana; Sri Wahyuningsih (Jurnal FARMASIMED (JFM), 2026)
Type 2 Diabetes Mellitus (T2DM) is a chronic disease characterized by elevated random blood glucose ≥200 mg/dL or fasting blood glucose ≥126 mg/dL, resulting from defects in insulin secretion, insulin action, or both. Type 2 Diabetes Mellitus constitutes a global health threat with a projection of 28.57 million cases in Indonesia, predicted to become a significant financial burden on the National Health Insurance System by 2045 with costs ranging from 1.6 Trillion to 3 Trillion Rupiah. This study analyzes the comparative effectiveness of Insulin versus Oral Antidiabetic Drug treatment patterns in BPJS outpatients through systematic literature review using PRISMA protocol through a primary article search on Google Scholar for the 2020-2025 period resulting in 309 articles, 299 articles did not meet the criteria for inclusive inclusion, and the remaining 10 articles continued to the assessment analysis stage. Findings reveal therapeutic equivalence of both modalities with non-significant Hba1c reduction difference (0.123%; P=0.608), yet Oral Antidiabetic Drugs demonstrate economic superiority with Metformin-Sulfonylurea combination being more Cost-Effective than Metformin-Insulin (P<0.001). Patient characteristics, comorbidities, and adherence significantly influenced therapeutic response, with 79% of patients demonstrating suboptimal glycemic control. Effectiveness variability was determined by institutional clinical protocols, and the INA-CBG rate of new-generation insulin achieved a profit margin of 3.30%. The Study provides empirical evidence for optimizing stepwise therapy algorithms prioritizing Oral Antidiabetic Drugs before Insulin Escalation within Indonesia's Health Coverage Context.